FORMATION OF A STATEMENT OF FINANCIAL POSITION AND METHODS OF ITS ANALYSIS - Arystanbek Aitkazinov (World Scientific Reports, 2023)
Financial reporting provides crucial information about an organization's activities to various user groups. To be effective, financial reporting must possess qualities such as reliability, completeness, materiality, and neutrality. Financial statements summarize an enterprise's financial and economic activities using accounting data. They are mandatory in most countries to provide information to users such as investors, lenders, government bodies, and employees. The balance sheet, also known as the statement of financial position, is a vital source of information for assessing an organization's financial condition and making management decisions. Proper analysis of an enterprise's financial condition begins with evaluating the balance sheet. The balance sheet helps identify deviations and necessary measures for improvement. Accurate, objective, and timely information from the balance sheet is essential for guiding and controlling an enterprise's activities. This article research focused on the balance sheet of "Das erste Haus" LLP, a company in Kazakhstan that specializes in roofing and facade solutions. The financial statements of the company comply with accounting and reporting laws, international standards, and the Tax Code. The purpose of the research is to explore the formation and analysis of key indicators in the balance sheet. The research tasks involve studying the concept and importance of the balance sheet, examining its accounts, analyzing the financial position using various methods, providing the characteristics of "Das erste Haus" LLP, and offering recommendations for improving its financial condition.